2005
DOI: 10.1016/j.physb.2005.01.369
|View full text |Cite
|
Sign up to set email alerts
|

Unconventional charge ordering in Na0.70CoO2 below 300K?

Abstract: We present the results of measurements of the dc-magnetic susceptibility χ(T ) and the 23 Na-NMR response of Na0.70CoO2 at temperatures between 50 and 340 K. The χ(T ) data suggest that for T > 75 K, the Co ions adopt an effective configuration of Co 3.4+ . The 23 Na-NMR response reveals pronounced anomalies near 250 and 295 K, but no evidence for magnetic phase transitions is found in χ(T ). Our data suggest the onset of a dramatic change in the Co 3d-electron spin dynamics at 295 K. This process is completed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
7
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 14 publications
1
7
0
Order By: Relevance
“…Computational studies using first principles methods [4][5][6][7][8][9][10][11][12][13][14] and low temperature experiments [15][16][17][18][19][20][21][22][23] have revealed that the fundamental physics originate from the peculiar two-dimensional layered structure of the crystal. The spin states of the edge-shared CoO 6 octahedra [20][21][22] that are responsible for high thermoelectric power, the nature of the covalent-like bonding between Co and O, 7,24 and the influence of Na ions on the electronic structure of the CoO 6 octahedra [9][10][11][12] have all been investigated. However, these factors are discussed only in terms of the Na content or the distortion of CoO 6 octahedra; to the best of our knowledge, apart from a report on the crucial role Na vacancies play in achieving low phonon thermal conductivity by our group, 25 no attention has been paid to the Na vacancies themselves, which are inevitably created when the Na content, x, is decreased from unity.…”
Section: Introductionmentioning
confidence: 99%
“…Computational studies using first principles methods [4][5][6][7][8][9][10][11][12][13][14] and low temperature experiments [15][16][17][18][19][20][21][22][23] have revealed that the fundamental physics originate from the peculiar two-dimensional layered structure of the crystal. The spin states of the edge-shared CoO 6 octahedra [20][21][22] that are responsible for high thermoelectric power, the nature of the covalent-like bonding between Co and O, 7,24 and the influence of Na ions on the electronic structure of the CoO 6 octahedra [9][10][11][12] have all been investigated. However, these factors are discussed only in terms of the Na content or the distortion of CoO 6 octahedra; to the best of our knowledge, apart from a report on the crucial role Na vacancies play in achieving low phonon thermal conductivity by our group, 25 no attention has been paid to the Na vacancies themselves, which are inevitably created when the Na content, x, is decreased from unity.…”
Section: Introductionmentioning
confidence: 99%
“…As we outline below our data are to some extent in conflict with previously published details of structural features of the Na sublattice, in particular if x < 1 [5]. Results of diffraction experiments were discussed in relation with models describing selected static vacancy arrangements [5,9]; aspects of the motion of Na-ions have been addressed to a much lesser extent [6,11]. Our results give clear evidence that the dynamics of the Na ions is a dominating factor for the understanding of these compounds at temperatures exceeding 200 K where a growing diffusion of the Na-ions sets in.…”
mentioning
confidence: 86%
“…It is desirable to directly probe the Na ions to confirm its dynamics. Indeed, in recent NMR studies on Na 0.7 CoO 2 powder, various anomalies in the Na NMR spectrum were seen in a similar T range [24]. ple crystallographic phases or the presence of paramagnetic volume in otherwise magnetically ordered samples [25,26,27].…”
mentioning
confidence: 93%